Selection and application of physical fitness evaluation tests for the U12 male football team at Nguyen Anh Thu Secondary School, District 12, Ho Chi Minh City - Ha, Nguyen Thi; Dat, Dinh Quoc (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2024)
Through the use of four traditional research methods including document synthesis, interviews, pedagogical testing, and statistical analysis with a sample of 12 male students, the study had synthesized documents, conducted interviews, and tested the reliability of the tests, selecting 10 physical fitness tests for the U12 male soccer team of the school with sufficient reliability (coefficient r > 0.8). The evaluation results of the physical fitness status of the U12 male soccer team of Nguyen Anh Thu Middle School, District 12, Ho Chi Minh City, show relatively consistent development. The mean value is highly consistent with a coefficient of variation (CV) < 10% and a relative error ε ≤ 0.005, indicating that these tests can represent the sample set. The selection and application of these tests to assess the physical fitness status of the U12 male soccer team are essential and practically significant for adjusting exercise content, training methods, and the volume and intensity of physical activity in a more scientific manner. This aims to enhance the training effectiveness and competitive achievements of the U12 male soccer team at Nguyen Anh Thu Middle School, District 12, Ho Chi Minh City.